The Justice and Development Party's identity and its role in the EU's decision to open accession negotiations with Turkey - Icener, Erhan; Cagliyan-Icener, Zeyneb (Routledge Journals, Taylor & Francis Ltd, 2011)
This paper investigates the identity of the Justice and Development Party (AKP) - the conservative-democratic party in power in Turkey since November 2002 - and assesses its role in the EU's decision to open accession negotiations with Turkey. It argues that the AKP leadership has successfully employed an identity-based strategy highlighting the possibility of being Muslim and sharing European norms and values at the same time and the importance of Turkey's EU membership to refute 'the clash of civilizations' thesis to get Turkey closer to the EU in the post-September 11 global political context.
Keywords: AKP; Turkey; identity; discourse; EU enlargement